2020
DOI: 10.1371/journal.pone.0228265
|View full text |Cite
|
Sign up to set email alerts
|

In Silico identification of angiotensin-converting enzyme inhibitory peptides from MRJP1

Abstract: Hypertension is considered as one of the most common diseases that affect human beings (both male and female) due to its high prevalence and also extending widely to both industrialize and developing countries. Angiotensin-converting enzyme (ACE) has a significant role in the regulation of blood pressure and ACE inhibition with inhibitory peptides is considered as a major target to prevent hypertension. In the current study, a blood pressure regulating honey protein (MRJP1) was examined to identify the ACE inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 92 publications
1
21
0
Order By: Relevance
“…This database contains over 4132 bioactive peptides and, as it is a comprehensive source of bioactive peptides, no other database was used in this study to assess the novelty of the identified peptides. The usability of in silico methods and databases such as BIOPEP-UWM in supporting the analysis of bioactive peptides derived from food sources was demonstrated previously by authors including Udenigwe [ 24 ], Tahir [ 25 ] and Minkiewicz and colleagues [ 19 ]. In this study, we used it to determine if the identified peptide sequences were novel, but further work to assess the bitterness and further bioactivities of the peptides could be determined using an in silico approach.…”
Section: Discussionmentioning
confidence: 95%
“…This database contains over 4132 bioactive peptides and, as it is a comprehensive source of bioactive peptides, no other database was used in this study to assess the novelty of the identified peptides. The usability of in silico methods and databases such as BIOPEP-UWM in supporting the analysis of bioactive peptides derived from food sources was demonstrated previously by authors including Udenigwe [ 24 ], Tahir [ 25 ] and Minkiewicz and colleagues [ 19 ]. In this study, we used it to determine if the identified peptide sequences were novel, but further work to assess the bitterness and further bioactivities of the peptides could be determined using an in silico approach.…”
Section: Discussionmentioning
confidence: 95%
“…In pharmaceutical research, computational strategies are of great value as they help in the identification and development of novel promising compounds especially by molecular docking methods [33,34]. Various research groups have applied these methods to screen potential novel compounds against a variety of diseases [35].…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme (ACE) has a significant role in the regulation of blood pressure and ACE inhibition with inhibitory peptides is considered as a major target to prevent hypertension [35]. Several studies have used docking approach to inhibit the expression of ACE protein with natura compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these areas are considered as the pillars of a new era in vaccine development. In advance era of research, bioinformatics and computational biology help to solve numerous biological problems through mathematical, computational and statistical approaches [6][7][8][9]. In the past few years, the medical community has faced the challenges of H1N1 influenza, Dengue, Ebola, Zika, and now SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%